2006
DOI: 10.1177/0255761406065475
|View full text |Cite
|
Sign up to set email alerts
|

Vernacular music-making and education

Abstract: This article examines the division of music styles according to the conventional categories of classical, traditional and popular, and proposes the term ‘vernacular’ as a complementary way of viewing various types of amateur music-making among diverse groups in modern societies. ‘Vernacular’, as it is used here, includes the idea of relatively distinct musical communities as well as more fluid networks and scenes. The article exposes the historical basis and problematic nature of style categorizations, and ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 9 publications
0
27
0
2
Order By: Relevance
“…Playing by ear, therefore, demands careful and attentive listening which, as is well known, is fundamental to most vernacular musics of the world, as well as many nonWestern classical traditions (Campbell, 1991;O'Flynn, 2006). McPherson s research (McPherson, 1995b(McPherson, , 1997McPherson & Gabrielsson, 2002) has also shown that ear-playing is directly connected with the skill of improvising, sight reading and playing from memory.…”
Section: Introductionmentioning
confidence: 99%
“…Playing by ear, therefore, demands careful and attentive listening which, as is well known, is fundamental to most vernacular musics of the world, as well as many nonWestern classical traditions (Campbell, 1991;O'Flynn, 2006). McPherson s research (McPherson, 1995b(McPherson, , 1997McPherson & Gabrielsson, 2002) has also shown that ear-playing is directly connected with the skill of improvising, sight reading and playing from memory.…”
Section: Introductionmentioning
confidence: 99%
“…To address this balance, a growing number of scholars have called for research on blended models of music education that incorporate both formal and informal teaching practices and include students from both formal and informal backgrounds (Feichas;Georgii-Hemming & Westvall, 2010;Green, 2006;Isbell, 2015;McPhail, 2013;O'Flynn, 2006). We recently observed one such blended formal/informal college music ensemble that we suggest holds implications for school music education.…”
Section: Blending Formal and Informalmentioning
confidence: 84%
“…We use the term blended formal/informal to describe an approach that scholars (Feichas, 2010;Georgii-Hemming & Westvall, 2010;Green, 2006;Isbell, 2015;McPhail, 2013;O'Flynn, 2006) have called for that incorporates both formal and informal practices and includes students from both formal and informal backgrounds. Finally, we use the term hospitality (Higgins, 2007a(Higgins, , 2007b(Higgins, , 2012 to contextualize the kind of environment the bandleader curates for music making and learning.…”
Section: Definitionsmentioning
confidence: 99%
“…The first year and other aspects of the project were funded by the Esmée Fairbairn Foundation with the support of the London University Institute of Education. 3 For current projects and commentaries concerning the adaptation of informal music learning practices within the formal realm, see for example: Allsup (2004), Boespflug (2004), Byrne (2005), Byrne and Sheridan (2000), Cope (1999) Cutietta (2004, Downey (2009), Dunbar-Hall (1996), Dunbar-Hall and Wemyss 2000, Emmons (2004), Evelein (2006), Feichas (2010), Folkestad (2006), Finney and Philpott (2010), Gatien (2009), Georgii-Hemming and Westvall (2010), Green (2001Green ( , 2008, Heuser (2008), Humphreys (2004), Jaffurs (2004), Jones (2008), Karlsen (2010), Lebler (2007Lebler ( , 2008, Lines (2009), Mans (2009), Marsh (2008), O'Flynn (2006, Rodriguez (2004Rodriguez ( , 2009, Seddon andBiasutti (2009, 2010), Siefried (2006), Väkevä (2006, Watkins (2010), Wemyss (2004), Westerlund (2006), Woody and Lehmann (2010), Wright and Kanellopoulos (2010). This list is not exhaustive and there are many other excellent references on this topic to be explored.…”
Section: Notesmentioning
confidence: 99%